Changes in LIF expression on PCOS as biomarker implantation - Uki Retno Budihastuti; Eriana Melinawati; Sri Sulistyowati; Tanti Arianti (Majalah Obstetri dan Ginekologi, 2021)
Objectives: This study aimed to compare the endometrial expression of LIF PCOS compared to normal and determine the effect of PCOS and external variables that affect LIF expression.Materials and Methods: This retrospective case control study with a correlational approach was conducted at Sekar Clinic, General Hospital Dr. Moewardi Surakarta. Subject were taken by consecutive sampling starting from September 2018 –. Februari 2019. External variable: age, occupation, family history PCOS, menarche, and BMI were recorded. The research samples were 60 subjects consisting of 30 PCOS patients based on Rotterdam criteria and 30 fertile women. In the luteinizing hormone (LH) secretion phase at LH + 5 days - LH + 10 days, an endometrial biopsy is performed with pipelle curettage, then it is examined by immunohistochemistry. Statistical analysis was performed using the Mann-Whitney, linier regression test.Results: Mean of LIF expression was found significantly lower in PCOS group (1.53±3.65) compared to control group (35.33±21.04, with p=<0.001). Multivariate analysis linear regression in the effect of PCOS and external variables to endometrial LIF expression models showed PCOS (b=-1.14; 95% CI=-1.56 – -0.72; p=<0.001) and occupation (b = 0.32; 95% CI=0.14 – 0.52; p=0.001) significantly decreases LIF expression. PCOS (B=-1.14) is more important than Occupation (B=0.33) in decreasing LIF expression.Conclusion:LIF expression decreased in the endometrium of PCOS patients and occupations compared to normal group, with considering all existing variables.